2020
DOI: 10.1111/jfpp.14734
|View full text |Cite
|
Sign up to set email alerts
|

Effect of flour processing on the proximate composition, polyphenolic content, and antioxidant activity of 19 Philippine sweet potato cultivars

Abstract: Sweet potato is the sixth most important food crop in the world after rice, wheat, potatoes, maize, and cassava (International Potato Center, 2020). Over 105 million tonnes have been produced annually between 2013 and 2017 (FAOSTAT, 2019a). In developing countries, it is considered as the fifth most important food crop (International Potato Center, 2020). It has a lot of development potential as it is a low input crop (labor and other resources), has a wide production geography, is highly adaptable to marginal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 44 publications
0
1
1
Order By: Relevance
“…However, tarwi flour values are much lower than those observed by the aforementioned authors. A total phenol content higher than that found in the present work was reported (110 µg GAE/mg extract) in water extract of achira (Canna indica) dried (45 • C) rhizomes from the banks of Cauvery River (Mysore, India), [32], and in camote flour (values ranged from 28 to 1228 mg GAE/100 g) from 19 Philippine varieties, grown in the same area and under similar conditions as to avoid possible differences due to these factors [15]. In lupinus grains from Ecuador (varieties INIAP-450, INIAP-451 and Criollo), Villacrés, et al [26] observed a significant decrease in some compounds (96.83% for phenols and 49.42% for carotenoids) during debittering and fermentation.…”
Section: Antioxidant and Total Phenol Contentcontrasting
confidence: 64%
See 1 more Smart Citation
“…However, tarwi flour values are much lower than those observed by the aforementioned authors. A total phenol content higher than that found in the present work was reported (110 µg GAE/mg extract) in water extract of achira (Canna indica) dried (45 • C) rhizomes from the banks of Cauvery River (Mysore, India), [32], and in camote flour (values ranged from 28 to 1228 mg GAE/100 g) from 19 Philippine varieties, grown in the same area and under similar conditions as to avoid possible differences due to these factors [15]. In lupinus grains from Ecuador (varieties INIAP-450, INIAP-451 and Criollo), Villacrés, et al [26] observed a significant decrease in some compounds (96.83% for phenols and 49.42% for carotenoids) during debittering and fermentation.…”
Section: Antioxidant and Total Phenol Contentcontrasting
confidence: 64%
“…These flours may or may not have similar properties to traditional flours, so Andean crop flours can be an alternative option to substitute traditional flours in the industry, considering as well their possible different applications. Most studies have referred to tubers or grains, or their starch, such as arracacha flour from Brazil [7], taro flour from Cuba [13], starch and flour of Brazilian camote [14], flour of the Philippines camote [15], flour and starch of taro from Thailand varieties [9] and Tarwi flour from Egypt [16]. However, there are few studies on the characterization of flours of some of these crops from the Andean region.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, previous studies have reported that synthetic food coloring has caused various and serious health problems such as mutations, disruption of hormones, cancers, hypofertility, and allergic reactions [3][4][5][6][7][8]. Natural plant colors play an important role in the food industry in the absence of toxicity and also have several beneficial effects for consumers [9][10][11][12][13][14]. Among these plants, red beetroot pigments have also been used as a natural colorant, aroma, and antioxidant in the food industry [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%